Times Optimization in the Installation of Loading Pipes in Underground Mining Operation - Sereno Ricse, Rolling Alex (2025)
Economic policies and the crisis caused by COVID-19 have harmed mining production, with minimal, slow, and conservative investments. An alternative to improve this is underground mining, which represents 43% of worldwide operations; however, the limited production and the number of accidents are limiting, so the procedure for the optimization of times and the time of exposure of workers to danger during the installation of loading tubes were evaluated. For this, the current and improved PAD and POD were analyzed (after the modification of the bit and loading tube), evidencing that in the current procedure, it takes 91 minutes for the installation, with an advance of two and a half cycles. In contrast, in the improved situation, it takes 23 minutes, reaching three cycles, concluding that there is an optimization of 68 minutes per cycle. The time of exposure to danger is also reduced by 2.8 hours.